2016
DOI: 10.3389/fpls.2016.00871
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profile Analysis from Different Sex Types of Ginkgo biloba L.

Abstract: In plants, sex determination is a comprehensive process of correlated events, which involves genes that are differentially and/or specifically expressed in distinct developmental phases. Exploring gene expression profiles from different sex types will contribute to fully understanding sex determination in plants. In this study, we conducted RNA-sequencing of female and male buds (FB and MB) as well as ovulate strobilus and staminate strobilus (OS and SS) of Ginkgo biloba to gain insights into the genes potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 73 publications
(81 reference statements)
2
21
1
Order By: Relevance
“…Besides, the annotated genes were enriched in the top ten GO enrichment categories ( Figure 3C). Our results are congruent with that eight categories i.e., "metabolic process", "cellular process", "response to stimulus", "catalytic activity", "binding", "cell part", "cell" and "organelle" are all densely enriched in the transcripts of female reproductive organs in Gingko [81] and conifers [82]. These results provide useful information to infer the conservative functional genes in regulating the development of female strobili in gymnosperms.…”
Section: Full-length Transcriptome and Gene Annotationsupporting
confidence: 87%
“…Besides, the annotated genes were enriched in the top ten GO enrichment categories ( Figure 3C). Our results are congruent with that eight categories i.e., "metabolic process", "cellular process", "response to stimulus", "catalytic activity", "binding", "cell part", "cell" and "organelle" are all densely enriched in the transcripts of female reproductive organs in Gingko [81] and conifers [82]. These results provide useful information to infer the conservative functional genes in regulating the development of female strobili in gymnosperms.…”
Section: Full-length Transcriptome and Gene Annotationsupporting
confidence: 87%
“…In our research, 80,765 unigenes were identified, and 50,981 unigenes were annotated in at least one database, which accounted for 63.12% of the total unigenes. The number of unigenes identified was more than twice that of some previous studies [ 38 , 40 ], but less than a previous study [ 39 ]. Because these studies utilized different plant tissues, the quality of the sequence data cannot be judged simply by the number of identified unigenes.…”
Section: Discussioncontrasting
confidence: 53%
“…Recently, with the development of next-generation sequencing technology, a number of transcriptome analyses in Ginkgo have been published [ 38 , 39 , 40 ]. However, these focused on the transcriptomes of sterile seedlings [ 40 ], kernels [ 38 ], and different sexual types [ 39 ] of Ginkgo. The transcriptome of the mature Ginkgo leaf, which is the most important organ for pharmaceutical industries, was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…One is to block the cell lumen to make it difficult for water to effectively defuse into the cell wall, so as to improve the dimensional stability and decay resistance of wood. The explored modification methods include filling wood cell lumen by physical or chemical means, such as physical filling with poly (glycidyl methacrylate) [27] or phenolic resin [28], physical or chemical filling with polyacrylic resin [29][30][31], or physical or chemical filling with inorganic silica compounds [32]. However, this strategy implies the use of large amounts of filler, resulting in high cost.…”
Section: Introductionmentioning
confidence: 99%